Information Technology Implementation in SMEs: A Comparison of Indonesia and Malaysia - Budhi Cahyono; Lutfi Nurcholis; Marno Nugroho (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2022)
Objective: The purpose of the study is to compare SMEs in Indonesia and Malaysia regarding the implementation of information technology, especially on the sustainable competitive advantage factors, IT adoption, perceived simplicity, green technology capability, and performance. Design/Methods/Approach: Survey data are collected from 269 SME leaders and managers SMEs in Indonesia and 241 respondents in Malaysia. The sampling model is purposive sampling while analysis involved a non-parametric test (Mann-Whitney U-test).  Findings:  The results show that there are significant differences for the variables SCA, SMEs performance expectation, and IT adoption. There are no significant differences between Indonesian and Malaysian SMEs for the variables of perceived simplicity and green technology capability. Originality: The paper contributes to the growing research on information technology implementation by using factors within Sustainable Competitive Advantage, IT adoption, perceived simplicity, green technology capability, and performance. Practical/Policy implication: This finding can encourage SMEs in Indonesia and Malaysia to work together to develop important variables to improve the implementation of information technology to increase competitiveness.